Ethics Education in Technical AI Programs: Toward a Complexity and Care-Based Approach - Aubin, Adèle (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2025)
Current initiatives to include ethics in artificial intelligence (AI) technical curricula are slow to bear fruit. This paper discusses several key challenges that undermine these pedagogical efforts to include ethics, namely the confusion around the meaning of AI ethics, a tendency to prioritize technical over social perspectives, and a lack of solid educational grounding. These challenges are further explored using humanities-based perspectives. Finally, potential answers based on the paradigm of complexity and the ethics of care are suggested in response to the identified pitfalls.